Repeat spawning of the Atlantic salmon (Salmo salar) in various salmon rivers in Iceland - Halla Kjartansdóttir 1978- (2008)
Information on repeat spawning in Atlantic salmon stocks from eight various rivers in Iceland was analyzed, using data collected by the Institute of Freshwater Fisheries in Iceland. The rivers differ in characteristics as well as location based on bedrock and geographical area. Available data from these rivers was compiled but to answer the hypothesis, data from 1989 through 2006 was utilized. From available data repeat spawning reached up to 33% of catches in Botnsá (1949) and down to no returning spawners some years in individual rivers. The average (mean) proportion of repeat spawning in individual rivers over the study period ranged from 3,0% (Norðurá) to 9,8% (Stóra-Laxá). There was significant difference of average (median) proportion previous spawners between Stóra-Laxá and Þjórsá and Stóra-Laxá and Laxá in Aðaldalur but not between the other rivers. There was only significant reduction on the proportion previous spawners with time in Laxá in Aðaldalur (p = 0,013) and nearly in Miðfjarðará (p = 0,052); but none of the other rivers. In those two rivers that are in the northeast, time (y) explained 33% of % previous spawners (x). Proportion repeat spawning when rivers were divided by bedrock type (rivers in Plio-Pleistocene vs. Tertiary) did not differ significantly (p = 0,717) but when divided up by geography (south and west versus north and east) there was a significant difference (p = 0,049). The average (mean) proportion of females amongst the previous spawners over the study period ranged from 45,1% (Stóra-Laxá) to 98,9% (Þjórsá) and of males amongst the previous spawners from 1,1% (Þjórsá) and 54,9% (Stóra-Laxá). There were significantly more females in Þjórsá, Sog, Botnsá, Norðurá and Flekkudalsá but not in Stóra-Laxá, Laxá in Aðaldalur and Miðfjarðará. Over all the study rivers the average (mean) proportion of females was 66,4% and males 33,0% with significantly more females (p = 0,001). When rivers were compaired there was significant difference of female/male proportion between Þjórsá and Laxá in ...